Co-infecção between syphilisand human papilomavirus: brokena vertical transmission chain - Souza, Lúcia M S; Nery, José C; Andrade, Arnaldo FB (Brazilian Journal of Sexually Transmitted Diseases, 2006)
A patient, male, 26 years old, married, with elementary school ship, lived in Duque de Caxias, Rio de Janeiro, Brazil, came for the clinical of SexuallyTransmited Disease (STD) in Rubem David Azulay Dermatology Institute in Santa Casa de Misericórdia, Rio de Janeiro, with the principal complaint of awart in his penis. After the first clinical evaluation, it was concluded that it was a case of human papilomavirus, the HPV. He was solicited complementaryexams to detect syphilis and he was advised to make a test to detect antibody for HIV, he was also suggested that it was important to bring his wife in the nextconsult for evaluation. When the syphilis test of VDRL (Veneral Disease Research Laboratory) was realized it was detected a title of 1:16, it was confirmedwith T.P.H.A.( Treponema pallidum Hemaglutination Assay), a treponema test. Unfortunately the patient didn’t come in the following consult, only regressingfive months later. In this occasion he brought his wife, she was five months of pregnancy. Both of them was treated in accord of the protocol of the HealthMinistry. In this Case of Study it was evidenced the relationship of co-infection in the sexually transmitted disease (STD).